PERSONIFICATION STORY ANALYSIS IN THE NOVEL DILAN: DIA ADALAH DILANKU TAHUN 1990 BY PIDI BAIQ - Dyah Nanda Dewi; Eva Eri Dia (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
This study analyzes personification figures in the novel Dilan: Dia is Dilanku Tahun 1990 by Pidi Baiq. The main objective of this research is to describe the personification of the novel Dilan: Dia is Dilanku Tahun 1990 by Pidi Baiq. This research is a descriptive study with a qualitative approach. The technique used in data collection in this study is observation. The instrument in this study was the researcher himself who was assisted by data collection tools. The data analysis was carried out by identifying the data, classifying the data, looking at the personification figures, and describing the results. The results showed that personification figures can be found in novels